2012
DOI: 10.2466/13.16.pr0.110.2.363-377
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Schools in Which Fatal Shootings Occur

Abstract: School-based violence, and fatal school shootings in particular, have gained increased attention in the media and psychological literature. Most reports have focused on the characteristics of perpetrators, but there is a growing awareness that school-related factors may also influence the occurrence of fatal school shootings. The current study examined several key characteristics of all schools where random (38) and targeted (96) fatal shootings occurred in the United States between 1966 and 2009. These were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…We found that NCAA athletes participating in higher divisions were at higher risk of homicide-related deaths. Prior studies indicate that schools with urban and suburban locations, larger enrolment, and public funding have positive association with fatal shootings 15. While D1 programmes are more likely to meet these criteria than lower division programmes, further inquiry is needed to evaluate this finding.…”
Section: Discussionmentioning
confidence: 99%
“…We found that NCAA athletes participating in higher divisions were at higher risk of homicide-related deaths. Prior studies indicate that schools with urban and suburban locations, larger enrolment, and public funding have positive association with fatal shootings 15. While D1 programmes are more likely to meet these criteria than lower division programmes, further inquiry is needed to evaluate this finding.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, just as observing violence in the home, school, and community increases the odds of aggression, so too can observing violence in the media. School characteristics. A number of studies have examined the characteristics of the school when a mass shooting takes place on school grounds (Baird, Roellke, & Zeifman, ; de Apodaca, Brighton, Perkins, Jackson, & Steege, ). Mass shootings are more likely to occur in schools with a large class size and a high student‐to‐teacher and student‐to‐counselor ratio.…”
Section: Environmental Risk Factors For Youth Violencementioning
confidence: 99%
“…The recent era of mass shootings on college and university campuses has enlightened academic, legislative, and professional leaders about the pressing needs regarding the safety and health of students, faculty, and staff regardless of campus size, focus, or mission (Apodaca, Brighton, Perkins, Jackson, & Steege, 2012;Bendlin, 2013;Eells & Rockland-Miller, 2011;Heiselt & Burrell, 2012;Kennedy, 2010;Kennedy, 2015;Randazza & Cameron, 2012). The college years can correspond to the peak onset of mental health symptoms, especially considering the added pressures and stressors that relate to academic studies (Mitchell, Kader, Haggerty, Bakhai, & Warren, 2013).…”
Section: Bit Implementation At a Two-year Collegementioning
confidence: 99%